The Existential and Poetic Meaning of Women in the Short Stories of Robert Musil (Knjiženstvo, journal for studies in literature, gender and culture, 2025)
This paper explores the role of female characters as mediators of individual and existential development of male protagonists in Robert Musil’s short stories. The analysis of “Grigia” and “The Portuguese Lady” demonstrates how female characters – even when they remain unacknowledged and unrecognized – function as key factors in revealing the meaning and significance within the male existence: it is through them that the protagonists are driven towards inner growth, while they also serve as a medium for the transcendental. In the two stories which we are focusing on (“Grigia” and “The Portuguese Lady”), the fate of Musil’s male protagonists portrays woman as idealized or objectified: the ideal other or a sexual object. Grigia is Homo’s intermediary to death, but also his lover in a time when she comes into contact with the archetype of the shadow, while the Portuguese Lady plays a crucial role in the process of von Ketten’s individuation, where the decisive role belongs to the development and integration of his feminine side. By interpreting “The Portuguese Lady” as an allegory of psychological development, in which archetypes such as the anima, animus, and shadow play a crucial role, we interpret the fantastical motif in the same key: the anthropomorphized and deified cat is understood as a miraculous influx of the feminine principle, initiating profound changes in all characters and resolving the love triangle. Drawing on C.G. Jung’s analytical psychology, Musil’s poetics, and the possibility of allegorical interpretation, this paper sheds light on the existential and poetic role of women: it becomes clear that there is a significant difference between the actual place of women in protagonists’ lives as opposed to those the protagonist believed they should occupy. Musil weaves archetypal content into these short stories, which is a key aspect of their mysterious nature, along with the critical role that Grigia and the Portuguese Lady assume in the protagonists’ lives.
Keywords: Robert Musil; “Grigia”; “The Portuguese Lady”; archetypes; feminine principle